Tuberculosis drug streptomycin as a potential cancer therapeutic: inhibition of miR-21 function by directly targeting its precursor - Bose, Debojit; Jayaraj, Gopal Gunanathan; Suryawanshi, Hemant; Agarwala, Prachi; Pore, Subrata Kumar; Banerjee, Rajkumar; Maiti, Souvik (Angewandte Chemie-International Edition, 2012)
Keywords: Apoptosis; drug discovery; Gene expression; inhibitors; RNA

Molecular-beacon-based screen for small molecule inhibitors of miRNA maturation - Bose, Debojit; Jayaraj, Gopal Gunanathan; Kumar, Santosh; Maiti, Souvik (ACS Chemical Biology, 2013)
miRNAs are small non-coding RNAs that regulate about 60% of mammalian genes by modulating their transcript levels. Network scale studies of miRNA-mediated regulatory circuits demonstrate the central importance of this class of small RNA in the maintenance of biological robustness. More recently, several reports have described the deregulation of numerous miRNA to be causally associated with many diseases, including cancer. These studies have highlighted the potential for development of therapeutic modalities against miRNA. Previous screening protocols, for small molecules targeting miRNA function, are either costly or technically too complex to be applied in a high-throughput manner in standard chemical laboratories. We describe a simple in vitro screening method using a DNA-based molecular beacon that overcomes the limitations associated with earlier screens. We used this method to identify inhibitors of miR-27a function from a library of 14 aminoglycosides as a pilot study. Inhibitory molecules identified were further scrutinized to identify the validity of screen. With this proof of concept we illustrate the utility of a scalable molecular-beacon-based screening strategy for miRNA inhibitors.

Anti-cancer therapeutic potential of quinazoline based small molecules via global upregulation of miRNAs - Nahar, Smita; Bose, Debojit; Panja, Sumit Kumar; Saha, Satyen; Maiti, Souvik (Chemical Communications, 2014)
Three quinazoline based small molecules showed global upregulation of miRNA expression with a selective enrichment of tumor suppressor miRNAs. The target genes of the upregulated miRNAs were predicted to be enriched for apoptotic pathways. Apoptotic induction following treatment with quinazoline compounds was confirmed by in cellulo studies. Thus, these small molecules having the core structural moiety (2,4-diphenyl-quinazoline) can be used as scaffolds to design activators of miRNA expression paving the way for novel anti-cancer drugs.

Cyclic cationic peptides containing sugar amino acids selectively distinguishes and inhibits maturation of pre-mirnas of the same family - Nahar, Smita; Bose, Debojit; Pal, Sudip; Chakraborty, Tushar Kanti; Maiti, Souvik (Nucleic Acid Therapeutics, 2015)
The discovery of microRNAs (miRNAs) has added a new dimension to the gene regulatory networks, making aberrantly expressed miRNAs as therapeutically important targets. Small molecules that can selectively target and modulate miRNA levels can thus serve as lead structures. Cationic cyclic peptides containing sugar amino acids represent a new class of small molecules that can target miRNA selectively. Upon treatment of these small molecules in breast cancer cell line, we profiled 96 therapeutically important miRNAs associated with cancer and observed that these peptides can selectively target paralogous miRNAs of the same seed family. This selective inhibition is of prime significance in cases when miRNAs of the same family have tissue-specific expression and perform different functions. During these conditions, targeting an entire miRNA family could lead to undesired adverse effects. The selective targeting is attributable to the difference in the three-dimensional structures of precursor miRNAs. Hence, the core structure of these peptides can be used as a scaffold for designing more potent inhibitors of miRNA maturation and hence function.

Selective inhibition of miR-21 by phage display screened peptide - Bose, Debojit; Nahar, Smita; Rai, Manish Kumar; Ray, Arjun; Chakraborty, Kausik; Maiti, Souvik (Nucleic Acids Research, 2015)
miRNAs are nodal regulators of gene expression and deregulation of miRNAs is causally associated with different diseases, including cancer. Modulation of miRNA expression is thus of therapeutic importance. Small molecules are currently being explored for their potential to downregulate miRNAs. Peptides have shown to have better potency and selectivity toward their targets but their potential in targeting and modulating miRNAs remain unexplored. Herein, using phage display we found a very selective peptide against pre-miR-21. Interestingly, the peptide has the potential to downregulate miR-21, by binding to pre-miR-21 and hindering Dicer processing. It is selective towards miR-21 inside the cell. By antagonising miR-21 function, the peptide is able to increase the expression of its target proteins and thereby increase apoptosis and suppress cell proliferation, invasion and migration. This peptide can further be explored for its anti-cancer activity in vivo and may be even extended to clinical studies.